Petrophysical characterization of the late-Variscan Santa Eulália Plutonic Complex (Ossa Morena Zone) - Sant'Ovaia, Helena (2012)
Petrophysical characterization of the late-Variscan Santa Eulália Plutonic Complex (Ossa Morena Zone) Sant’Ovaia, H.1, Nogueira, P.1,2, Carrilho Lopes, J.2,3, Fonseca, A.2, Sardinha, R.2, Lopes, L.2, Martins, H.1, Noronha, F.1 1: Universidade do Porto, Portugal; 2: Universidade de Évora, Portugal; 3: Universidade de Lisboa, Portugal The Santa Eulália Plutonic Complex (SEPC) is a calc-alkaline granitic body that occupies an area of 400 km2 and is located in the northern part of the Ossa Morena Zone of the Variscan Iberian sector, near the limit of the Central Iberian Zone. SEPC is considered as late-Variscan because it cross-cuts the regional variscan structures. The host rocks of the complex are composed by metamorphic formations from Proterozoic to Lower Paleozoic. The SEPC has two main facies which present different compositions and textures. From the rim to the core, there is a medium- to coarse-grained pinkish granite (G0) involving large masses of mafic to intermediate rocks and a central gray monzonitic granite (G1). The central facies can be divided into a porphyritic facies (G1A) and a central medium-grained facies (G1B). Petrography, mineralogy and whole-rock chemistry reveal clear differences between pinkish facies closer to I-type granites, and central gray facies similar to S-type granites. A preliminary study of the Anisotropy of Magnetic Susceptibility (AMS) was conducted to acquire a petrophysical characterization of these granitoids. This study was based on 50 sampling sites where 8 specimens per station were available. The measurements were made in Porto using a KLY-4S Kappabridge susceptometer (AGICO). A sequence of 3 susceptibility measurements along different orientations of each specimen allowed us to compute the orientation and magnitude of the three main axes k1 / k2 / k3 of the AMS ellipsoid. For each site, the AGICO software enabled us to calculate the mean susceptibility Km and the intensities and orientations of the three axes K1 / K2 / K3, which are its tensorial means. K1, the long axis of the mean ellipsoid, is the magnetic lineation of the site and K3, the short axis, is the normal to the magnetic foliation. P%, the magnetic anisotropy, corresponds to (K1/K3-1)*100 and T, expressed by (2 ln (K2/K3)/ln(K1/K3))-1 is the shape parameter of the AMS ellipsoid. The Km values range between 55.09 and 7343.67 x 10-6 SI. Two major groups can be established: facies G0, with Km > 10-3 SI which supports the presence of magnetite, and the central facies (G1A, G1B) with Km< 10-4 SI. In the central facies the paramagnetic behaviour is due to ferromagnesian minerals, such as biotite, and ilmenite. P% ranges between 2.2 and 18.2% being in mean >5% in facies G0 and <4% in the central facies (G1A, G1B). The high P% in G0 facies may be caused by the fact that the magnetite, which has a high susceptibility, is the bearer of the magnetic signal. Therefore a weak alignment of magnetite grains leads to a higher anisotropy of the rock. Nevertheless, microscope observations show signs of a post-magmatic deformation in G0. T ranges between -0.015 and 0.600 with the strongest oblate AMS ellipsoids in central facies and the slightly oblate in G0. The magnetic foliations are subvertical E-W-striking in G0 and G1A granites and NESW- striking with moderated SE dips in G1B. Magnetic lineations are subvertical in G0 and plunge moderated to the SW in G1A and to the South in G1B. These preliminary data support that the facies G0 and the central facies (G1A, G1B) have a distinct magnetic behaviour which may suggest different redox conditions in magma genesis. The magnetic fabric patterns may reflect different emplacement mechanisms.